FENOMENA PERILAKU SELF DISCLOSURE MELALUI PENGGUNAAN SECOND ACCOUNT INSTAGRAM PADA MAHASISWA ATMA JAYA ANGKATAN 2021 - Girsang, Diah Sintia (Jurusan Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jenderal Soedirman, 2024)
Sophisticated technology presents a variety of interesting features for users, namely the freedom feature to comment, both people you know and even strangers. The social media platform that is popular among the younger generation is Instagram, the number of users has increased enough to become popular on Instagram. The second account or another term, namely the second account, is private (locked) even followers are only friends who are considered close, limited and selected friends who can see their own life, so users of the second account will be free to upload posts on their account. This study uses descriptive qualitative analysis with the theory of self-disclosure and syringes. The results of this study are that one's mentality and feelings on social media are very important, freedom in social media must be considered, especially we as communicators who send messages need to consider whether it can hurt other people's feelings or not.